The diversity of fish species and the disturbances in the Cikawung river, Cianjur, West Java, Indonesia - RUHYAT PARTASASMITA; TONI NUARI; TATANG SUHARMAN ERAWAN; JOHAN ISKANDAR (Smujo International, 2015)
Abstract. Partasasmita R, Nuari T, Erawan TS, Iskandar J. 2015.The diversity of fish species and the disturbances in the Cikawung river, Cianjur, West Java, Indonesia. Nusantara Bioscience 7: 171-176.The diversity of fish species in the Cikawung river, the south coast of West Java, Indonesia plays a very important role for the villagers around the river. This river is an important source of animal protein for villagers of Karangwangi, Cidaun, Cianjur, West Java, Indonesia. The river flow is partially included in the Bojonglarang Jayanti Natural Reserve area. Based on the information given by the local residents, the Cikawung river used to have many species of fish 15 years ago, but now the population find it very difficult to get the fish in the river. People suspect that it is related to the frequency of fishing in various ways such as nets, fishing rods and even toxic chemicals. The object of this study is to determine the diversity of fish species in the Cikawung river and its disturbances as well as preservation and traditional conservation efforts by local residents. The study was conducted at inside and outside the natural reserve. The method used is a combination of quantitative and qualitative methods. The quantitative data gathering was performed by using structured interviews with 86 respondents that were chosen randomly among residents in the vicinity of the Cikawung river, using questionnaires. The results show that there are 32 species of fish, consisting of 22 species in the natural reserve, and 20 species outside the conservation areas. There are only 10 species of fish that found inside the natural reserve, while there are only 9 species of fish species found outside. It is found that there is 76% of the species of fish that is extremely rare, while the fish that are commonly found is Aplocheilus panchax and Puntius binotatus. The existence of fish tends to be very rare due to the fishing activities that continue to occur and the intensive use of pesticides. The decline in species diversity and abundance of fish species in the Cikawung river initiate local government and community leaders to make the arrangement of the use of Cikawung river as traditional conservation areas with the issuance Karangwangi Village Regulation (Perdes).